Winning in straight sets helps in Grand Slam tennis - Goossens, D. R.; Kempeneers, J.; Koning, R. H.; Spieksma, F. C. R. (International Journal of Performance Analysis in Sport, 2015)
In this contribution, we study whether fatigue resulting from the previous match affects a player's chances of winning his (or her) next match in Grand Slam tennis. We measure relative fatigue levels of two opponents by looking at the difference in number of sets played in their previous match. We develop two approaches to answer this question: the so-called carry-over method and the more common logit model. Both methods differ in the assumptions they make and the type of results they offer. Our results are based on data collected from the 4 Grand Slam tournaments (men and women) from 1992 till 2011, covering 20,320 matches. We find that there is indeed an impact of the relative effort invested in winning a match on the probability of winning the next match in a Grand Slam tournament. For women, having played one set more in the previous match than the opponent in her previous match, leads to a decreased winning probability. For men, this is the case only for a set difference of two. Our results show that this effect is present in each of the grand slam tournaments and does not vary with the surface type.